Rancang Bangun Aplikasi Pengelolaan Data Harga Pangan Di Dinas Ketahanan Pangan Provinsi Kalimantan Tengah Berbasis Web - Tayah, Hernila; Priskila, Ressa (Journal of Information Technology and Computer Science, 2021)
Technological developments greatly affect all aspects of human life, one of which is in the field of government. Currently, the food distribution sector in the food price division at the Central Kalimantan Province Food Security Service still uses excel as a medium for managing price data for reporting. This causes several problems, namely the processed data has not been integrated so that it takes time to process the price data recapitulation at the Service, slows down the performance of employees in making reports, and the risk of losing data is quite large. To overcome this problem, an application was made that can help employees/agencies to manage integrated food price data, search and make reports online through the website. The purpose of this research is to design and build a web-based food price data management application at the Food Security Service of Central Kalimantan Province. The system development method used in this research is the waterfall model, with the stages of Requirements Analysis and Definition, System and Software Design, Implementations and Unit Testing, Integration and System Testing, and Operation and Maintenance. Modeling systems and databases using Data Flow Diagrams and Entity Relationship Diagrams. This application consists of 2 (two) users, namely the provincial admin and the district admin. This application helps employees/agencies to manage food price data, search and report generation more easily and accurately.